2020
DOI: 10.1002/ppul.24715
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization dynamics associated with respiratory syncytial virus during early childhood

Abstract: Respiratory syncytial virus (RSV) is an important cause of early life acute respiratory infections. Potentially pathogenic respiratory bacteria, including Streptococcus pneumoniae, Moraxella catarrhalis, and Haemophilus influenzae are frequently detected during RSV infections and associated with increased illness severity. However, the temporal dynamics of bacterial colonization associated with RSV infection remain unclear. We used weekly nasal swab data from a prospective longitudinal birth cohort in Brisbane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Respiratory viruses such as HRV and RSV can trigger an outgrowth, rather than a new acquisition of S. pneumoniae and M. catarrhalis from the resident microbial community [49], as well as enhance their adherence to the respiratory epithelium by upregulating the expression of bacterial adhesion molecules such as fibronectin and platelet-activating factor receptor [50], which in turn facilitate secondary bacterial infection [51], and depress innate immune responses such as neutrophil and natural killer cell recruitment [52]. HRV was also shown to induce impairment on epithelial proliferation and promote airway remodeling [53].…”
Section: Nasal Viromementioning
confidence: 99%
“…Respiratory viruses such as HRV and RSV can trigger an outgrowth, rather than a new acquisition of S. pneumoniae and M. catarrhalis from the resident microbial community [49], as well as enhance their adherence to the respiratory epithelium by upregulating the expression of bacterial adhesion molecules such as fibronectin and platelet-activating factor receptor [50], which in turn facilitate secondary bacterial infection [51], and depress innate immune responses such as neutrophil and natural killer cell recruitment [52]. HRV was also shown to induce impairment on epithelial proliferation and promote airway remodeling [53].…”
Section: Nasal Viromementioning
confidence: 99%
“…Recent work has shown that most infants are already colonized by pneumococci at the time that they contract RSV ( 25 ). Additionally, children in low- and middle-income settings are often colonized by pneumococci early in life ( 8 ) and are therefore also likely to carry pneumococci at the time of viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most pneumococcal serotypes colonising the nasopharynx can cause lower airway infection ( 48 ). Even if initially a viral infection, secondary bacterial infection may ensue as bacterial densities increase further within the upper airways ( 63 ), especially in high-risk, heavily colonised. First Nations children ( 64 ) and those with a history of recurrent ALRIs.…”
Section: Discussionmentioning
confidence: 99%